Saberes tradicionais e propriedade intelectual: utopia ou possibilidade de proteção na perspectiva do novo constitucionalismo latino-americano - Ritter, Giane da Silva (2017)
In the era of globalization and the information society of the biotechnology sectors has had remarkable expansion and economic discourse. In this sense, today, ensure the monopoly of resources and important information in maintaining power over markets and consumers. Thus, as a basis for the promotion of biotechnology, Northern Social, natural resources, and the necessary information, the traditional knowledge, riches belonging to the Social South, is a classic expression of the relations of coloniality and subservience. In this way, traditional knowledge and biodiversity are constantly coming out of the Social North, appropriate for the Social North, the reason for quality is a need for dialogue on the need to build a normative instrument capable of granting effective protection to this wealth Of the social South. In this way, the present work has as scope to analyze the possibility of new epistemologies and orientations of protection to the traditional knowledge and associated biodiversity from the perspectives, foundations, principles and objectives of the new Latin American constitutionalism of Bolivia and Ecuador - from a View from the South - they are able to counteract a normative structure of agreement There are no comments on this or other items about it or for which they are interested in copyright. From the globalized world system. It is questioned, therefore, is this perspective of tutela from the look to a utopia or a possibility to be satisfied. In the meantime, in order to solve as questions and objectives of the present work, the research methodology in the trinamento: Base Theory / Approach, Procedure and Technique. Thus, as a base theory and approach, a dialectical perspective will be used, from which several conflicts between the new Latin American constitutionalism of Bolivia and Ecuador and the intellectual property instruments, Trips, and CBD have been established. Finally, as the procedure was adopted a bibliographic and documentary research and a technique used for the construction of archives and extended abstracts.